Treatment patterns, adherence to international guidelines, and financial mechanisms of the market access of advanced breast cancer therapy in Bulgaria - Karanyotova, Stephanie; Topova, Branimira; Petrova, Elina; Doychev, Peter; Kapitanska, Eliana; Petrova, Guenka; Mitkova, Zornitsa; Dimitrova, Maria (Frontiers in Public Health, 2023)
Introduction Breast cancer is the most common type of cancer affecting women in Europe. Advanced breast cancer (ABC) poses a significant therapeutic challenge, and therefore, timely access to treatment is crucial. The aim of the present study was to evaluate the treatment patterns and patients' access to new therapies for ABC in Bulgaria. Methods We conducted a retrospective study in the period 2008–2021. Based on the European Medicines Agency (EMA) database, we analyzed a number of medicinal products with marketing authorization for ABC in the last 13 years. Time to market access was evaluated as the degree of availability, which is measured by the number of medicines that are available to patients (availability index, AI), and the average time elapsed between obtaining a marketing authorization and time to inclusion in the Positive Drug List. Data were analyzed through descriptive statistics via Microsoft Excel version 10. Results The average time to access was 564 days for targeted therapy. The availability and compliance index for chemotherapy and hormonal therapy in advanced breast cancer was 1, while the average AI for targeted therapy was 0.67. Patient access to targeted oncology therapy of ABC is above average for Europe and takes 1–2 years. Conclusion Faster access is more evident for biosimilars. National regulatory requirements for pricing and reimbursement have a major impact on market access.